2020
DOI: 10.12943/cnr.2018.00002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Typical Thorium Impurities on Thorium-Based Nuclear Fuels

Abstract: Natural thorium contains impurities of numerous isotopes. A study was performed to examine the influence of naturally occurring impurities in thorium-based fuels on a few parameters of interest such as: exit burnup, coolant void reactivity (CVR), fuel temperature coefficients (FTC), and the radiotoxicity of the used fuel. Two different fuel bundle designs were modeled: a 43-element bundle containing 2.25% U-233, and a 35-element bundle containing 1.45% U-233. Naturally occurring thorium fuel impurities were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Thorium is considerably more abundant than uranium in the Earth's crust, so the use of thorium in power reactors has been considered since the start of nuclear energy in the 1950s (Kazimi, 2003). Thorium is said to be 'fertile' rather than 'fissile', as a quantity of Th 232 transforms into U 233 by absorbing neutrons within a reactor (Alexander et al, 2020). The breeding of U 233 from thorium is much more efficient than the breeding of Pu 239 from U 238 because of less production of non-fissile isotopes, which plays an important role in assessing the breeding capability of a nuclear reactor design, as a measurement of the potential for converting non-fissile material into fissile material through the use of neutron irradiation.…”
Section: Thorium As Future Nuclear Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorium is considerably more abundant than uranium in the Earth's crust, so the use of thorium in power reactors has been considered since the start of nuclear energy in the 1950s (Kazimi, 2003). Thorium is said to be 'fertile' rather than 'fissile', as a quantity of Th 232 transforms into U 233 by absorbing neutrons within a reactor (Alexander et al, 2020). The breeding of U 233 from thorium is much more efficient than the breeding of Pu 239 from U 238 because of less production of non-fissile isotopes, which plays an important role in assessing the breeding capability of a nuclear reactor design, as a measurement of the potential for converting non-fissile material into fissile material through the use of neutron irradiation.…”
Section: Thorium As Future Nuclear Fuelmentioning
confidence: 99%
“…India is the only country today extracting thorium from monazite which has been announced (International Atomic Energy Agency, 2019). Another concern is the presence of naturally occurring impurities in thorium-based fuels, but studies have found that the effect of impurities at their typical levels has a limited impact on fuel performance (exit burnup and radiotoxicity), thus not necessitating further refinement (Alexander et al, 2020).…”
Section: Global Thorium Resourcesmentioning
confidence: 99%
“…Thorium (232Th) is a radioactive element that can capture neutrons and become 233Th, which then undergoes double beta decay to produce fissile 233U, a nuclear fuel (5). Besides, some of the Th232 transforms into U233 by absorbing neutrons inside a reactor, which is why thorium is classified as "fertile" instead of "fissile" .Uranium-232 is preferred over uranium-238 for producing waste that does not contain longlived emitters because it hardly produces plutonium or other transuranic elements (6). Furthermore, adding thorium to ADS allows transuranium or plutonium to burn without requiring uranium-238.…”
Section: • Uraniummentioning
confidence: 99%
“…There is always a constant fear of the proliferation of these nuclear materials and there is a focus on fuel that can be proliferation resistant. Thorium is thus another nuclear energy fuel resource that is nearly three to four times as abundant as uranium, 8,9,10 and that it can be harnessed to augment, extend, or eventually replace uranium resources, where new reactor concepts are based on thorium are being studied/constructed. The PWR pin cell was therefore selected for analysis, to study the effect of detailed burn‐up data and reaction‐wise energy release incorporated in MCNP6.2 and DRAGON5 for fuels based on thorium.…”
Section: Introductionmentioning
confidence: 99%